2013
DOI: 10.4067/s0034-98872013000700002
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevida a largo plazo en adultos inmunocompetentes mayores de 60 años hospitalizados por neumonía adquirida en la comunidad

Abstract: (Rev Med Chile 2013; 141: 831-843).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…This result is similar with previous studies conducted in community-acquired pneumonia patients [ 14 ], which found that HRQOL was persistently lower in community-acquired pneumonia patients compared to non-diseased persons. Recent studies recognize long-term adverse outcomes associated with pneumonia, including mortality [ 35 ] and reduced HRQOL [ 36 ]. Peyrani and colleague argued that patients surviving an episode of community acquired pneumonia were still at increased risk of death long after hospital discharge [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar with previous studies conducted in community-acquired pneumonia patients [ 14 ], which found that HRQOL was persistently lower in community-acquired pneumonia patients compared to non-diseased persons. Recent studies recognize long-term adverse outcomes associated with pneumonia, including mortality [ 35 ] and reduced HRQOL [ 36 ]. Peyrani and colleague argued that patients surviving an episode of community acquired pneumonia were still at increased risk of death long after hospital discharge [ 37 ].…”
Section: Discussionmentioning
confidence: 99%